Reformasi Hukum Keluarga Islam di Indonesia dan Malaysia: Studi Perbandingan Sistem Hukum, Kelembagaan Peradilan, dan Perlindungan Hak Keluarga - Noor Asya; Veronita Indira Jayatri; Yasrina Esia Nur; Aulil Amri (TAQNIN: Jurnal Syariah dan Hukum, 2026)
The reform of Islamic family law in Southeast Asia has developed through different legal and institutional approaches, particularly in Indonesia and Malaysia, despite both countries sharing the same foundation in Islamic legal principles. Previous studies have predominantly examined specific aspects of family law reform, such as marriage, divorce, or judicial institutions, without comprehensively integrating the dimensions of legal systems, judicial institutions, and family rights protection within a comparative analytical framework. This study aims to analyze the reform of Islamic family law in Indonesia and Malaysia by comparing their legal systems, judicial institutions, and legal policies, as well as examining their implications for the protection of family rights. This research employs normative legal research using statutory, conceptual, and comparative approaches. Legal materials consist of legislation, judicial decisions, books, and recent scholarly articles on Islamic family law reform. The collected materials were analyzed qualitatively through comparative legal analysis. The findings reveal that Indonesia adopts a codified and nationally unified legal system that emphasizes legal certainty, whereas Malaysia applies a decentralized model that grants broader judicial discretion to the Syariah Courts. These differences significantly influence the regulation of marriage, polygamy, divorce, matrimonial property, and child custody, while both systems share the common objective of strengthening the protection of women’s and children’s rights. This study proposes an Integrative Islamic Family Law Reform Model, which synthesizes legal certainty, judicial flexibility, and family rights protection into a comprehensive conceptual framework for future Islamic family law reform in Muslim-majority countries. The study contributes to the development of comparative Islamic family law by demonstrating that effective legal reform requires the harmonization of legal substance, judicial institutions, and legal culture.